2020
DOI: 10.1007/s40618-020-01265-x
|View full text |Cite
|
Sign up to set email alerts
|

Monthly fluctuations in 25-hydroxy-vitamin D levels in day and rotating night shift hospital workers

Abstract: Purpose Epidemiological studies have suggested that indoor hospital employees, either day or night shift workers, are at high risk of metabolic and cardiovascular diseases. Interestingly, previous reports have also described a higher prevalence of vitamin D (25OHD) deficiency among these workers. However, few studies have determined the monthly variations in 25OHD levels in indoor hospital employees. Methods To address this lack of knowledge, in 2018, during the periodic health surveillance checks at the Servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Our preliminary results suggest that r-NSWs are at greater risk of COVID-19 infection risk, thus indicating another possible negative health consequence associated with shift work [3,4], which, in the health care sector, accounts for approximately 45% of workers. Despite its economic and social relevance, shift work results in a disruption of biological rhythms, thus predisposing individuals to poor metabolic health by promoting excess caloric intake and/or decreasing energy expenditure in response to reduced sleep [5].…”
Section: Discussionmentioning
confidence: 78%
“…Our preliminary results suggest that r-NSWs are at greater risk of COVID-19 infection risk, thus indicating another possible negative health consequence associated with shift work [3,4], which, in the health care sector, accounts for approximately 45% of workers. Despite its economic and social relevance, shift work results in a disruption of biological rhythms, thus predisposing individuals to poor metabolic health by promoting excess caloric intake and/or decreasing energy expenditure in response to reduced sleep [5].…”
Section: Discussionmentioning
confidence: 78%
“…Despite its economic and social relevance, shift work results in a disruption of biological rhythms, thus predisposing individuals to poor metabolic and cardiovascular health in response to reduced sleep. In fact, the literature indicates that NSWs are often affected from cardio-metabolic disorders [ 6 , 7 , 27 , 28 ] due to unhealthy behavioral factors, such as hyper-caloric diet, sedentarism and obesity. Accordingly, we have recently reported that HCWs with a “dysfunctional circadian clock” and with increased levels of IL1b carry a higher risk of developing carotid atherosclerosis through an overload of IL6 being released [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, night shift workers’ behavioral and environmental cycles are typically misaligned relative to the endogenous circadian system. Therefore, compared with day workers, NSWs have an increased risk of cardiovascular and metabolic disease [ 4 , 5 , 6 , 7 ], but, interestingly, recent published studies have also reported that NSWs have slight immunological disorders, such as unbalanced levels of circulating monocytes, T-lymphocytes and immunological biomarkers [ 8 , 9 ]. However, the impact of circadian rhythm disruption on the persistence of immune response following vaccination remains unclear [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the application of phototherapy in skin diseases, phototherapy has been widely applied for many diseases, including mental disorders [24,25], sleep disorders [26,27], and neurological disorders [28,29]. In addition, phototherapy is suitable for shift workers, such as rotating night-shift hospital workers who have a higher risk of vitamin D 3 insufficiency/deficiency [30]. Well-designed studies using phototherapy for shift workers have been conducted at the National Aeronautics and Space Administration (NASA), and treatment subjects have reported better sleep, performance, and physical and mental well-being than control subjects due to the adjustment of circadian rhythms [31][32][33].…”
Section: Phototherapy For Active and Healthy Aging: History And Current Applicationsmentioning
confidence: 99%